Fulminant Hepatic Failure Following Intentional Iron Overdose—A Case Report - Hrithik Dakssesh Putta Nagarajan; Ram Vivek Ramamoorthy; Naveen Vishwanath; Miruthula Murugan; Balakrishnan Kamaraj; Shiva Jeyaprakash Narayan Balamurugan; Shubham Kumar; Shilpa Gaidhane; Sanjit Sah; Prakasini Satapathy; Rachana Mehta; Amogh Verma (Clinical Case Reports)
ABSTRACT Intentional iron overdose in adults is a rare but formidable clinical challenge, often complicated by delayed presentation and a concealed history of ingestion. We report the case of a 21‐year‐old male who presented 4 days after consuming large quantities of ferrous sulfate tablets. The initial nonspecific gastrointestinal symptoms progressed to severe jaundice, encephalopathy, and coagulopathy, and the diagnosis was confounded by the patient's denial of suicidal ingestion. By the time iron toxicity was identified, the therapeutic window for early decontamination or parenteral chelation had been passed. Supportive care, including advanced extracorporeal therapies, facilitated hepatic and renal recovery. This case highlights the importance of high clinical suspicion, thorough history taking, and the potential role of salvage therapies in severe late‐presenting iron poisoning.